2002
DOI: 10.1007/bf02376045
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability in partially substituted lithium manganese spinel oxide cathode

Abstract: Abstract. LiMn204 is one of the most promising cathode materials for lithium secondary battery because of natural abundance of manganese in the crust and its low toxicity to environment.Lithium ion can almost reversibly intercalate into or deintercalate fxom lithium manganese spinel oxide LiMn204. A part of substitution of manganese with other transition metals brings the improvement of cycle life. We focused on the local structure of the spinels and considered the effect of the local distortion on the cycle l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…The observed potential peaks of the samples are compared in Table 4. In the 4 V region, extraction and insertion of Li + ions take place with a two-step reversible reaction; from LiMn 2 O 4 to Li x Mn 2 O 4 and then to k-MnO 2 [20,34,37]. However, anodic and cathodic peaks for Thirunakaran et al [25] observed that capacity changes were not directly proportional with boron content as shown in our results.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The observed potential peaks of the samples are compared in Table 4. In the 4 V region, extraction and insertion of Li + ions take place with a two-step reversible reaction; from LiMn 2 O 4 to Li x Mn 2 O 4 and then to k-MnO 2 [20,34,37]. However, anodic and cathodic peaks for Thirunakaran et al [25] observed that capacity changes were not directly proportional with boron content as shown in our results.…”
Section: Resultscontrasting
confidence: 62%
“…The diffraction peaks of the samples, where x varied between 0.1 and 0.4, are indexed to a cubic spinel structure of LiMn 2 O 4 with Fd-3m space group, which is consistent with JCPDS Card No: 01-088-1026. In this spinel structure, 32 oxide ions form a face centered cubic lattice, and the lithium and manganese ions occupy 8a tetrahedral sites and 16d octahedral sites, respectively [34]. XRD patterns show that the peaks were slightly shifted by the replacement of the Mn with B in the structure.…”
Section: Resultsmentioning
confidence: 98%
“…Electrochemical reaction at around 4 V implies that intercalation and deintercalation of Li þ ions proceed through cubic phase Li x Mn 2 O 4 where 0 < x < 1. Peaks at 3 V are the sign for excess Li in the spinel structure that cause the phase transformation from spinel LiMn 2 O 4 to rock salt Li 2 Mn 2 O 4 which belongs to tetragonal crystal lattice, where lithium ions occupy in 16c octahedral sites [27,28]. The CV curve of LiCu 0.2 Mn 1.8 O 4 displays the two symmetrical couples of redox peak at around 4 and 4.15 V which indicates the two step reversible extraction and insertion of Li þ ions in the spinel [27,29].…”
Section: Resultsmentioning
confidence: 99%
“…Another commercially available material, spinel-structured LiMn 2 O 4 , is much cheaper and less toxic. However, it is less stable during cycling [3,4], and thus, its usage is restricted.…”
Section: Introductionmentioning
confidence: 97%
“…Concerning the oxide Li-Mn-Co system, several mixed spinel oxides were synthesized with a part of the Mn atoms being replaced by Co atoms [6,[11][12][13][14]. Some of such compounds were found to be electrochemically active in the potential range up to 5 V versus Li.…”
Section: Introductionmentioning
confidence: 99%